The psychological impact of the coronavirus disease pandemic on hospital workers in Daegu, South Korea (2020)
Objective: This study aimed to assess the immediate stress and psychological impact experienced by healthcare workers and other personnel during the Coronavirus disease (COVID-19) pandemic. Method: The sample consisted of 2554 hospital workers (i.e., physicians, nurses, allied health professionals, and auxiliary staff members) who were working in Yeungnam University Hospital in Daegu, South Korea. The Impact of Event Scale-Revised (IES-R) was administered to the hospital workers twice over a 2 week interval. A high-risk group, identified on the basic of first total IES-R, was assessed further with the Mini International Neuropsychiatric Interview (MINI) and the Clinical Global Impressions-Severity (CGI-S) scale and was offered periodic psychiatric consultations on a telephone. Results: The participating nurses and auxiliary staff members had significantly higher IES-R scores (p < 0.01) than the physicians. During the second evaluation, the IES-R scores of the high-risk participants had decreased by 13.67 ± 16.15 points (p < 0.01), and their CGI-S scores had decreased by 1.00 ± 0.74 points (p < 0.01). The psychological symptoms of the high-risk group who received telephone-based psychiatric consultation showed improvement after 2 weeks. Conclusions: The present findings suggest that hospital workers experience high levels of emotional stress during a pandemic. In particular, the present findings underscore the need to provide more information and support to nurses and other administrative workers. There is a need for greater awareness about the importance of mental health care among hospital workers, and rapid and ongoing psychiatric interventions should be provided to workers during the pandemic period.